Phenotypic flexibility and the evolution of organismal design - Piersma, Theunis; Drent, Jan (Trends in ecology & evolution (Amsterdam), 2003)
Evolutionary biologists often use phenotypic differences between species and between individuals to gain an understanding of organismal design. The focus of much recent attention has been on developmental plasticity – the environmentally induced variability during development within a single genotype. The phenotypic variation expressed by single reproductively mature organisms throughout their life, traditionally the subject of many physiological studies, has remained underexploited in evolutionary biology. Phenotypic flexibility, the reversible within-individual variation, is a function of environmental conditions varying predictably (e.g. with season), or of more stochastic fluctuations in the environment. Here, we provide a common framework to bring the different categories of phenotypic plasticity together, and emphasize perspectives on adaptation that reversible types of plasticity might provide. We argue that better recognition and use of the various levels of phenotypic variation will increase the scope for phenotypic experimentation, comparison and integration.